Anteseden Keterikatan Karyawan - Maemar Chadavid Syamtar; Iin Mayasari (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
The purpose of this study was to test a relationship between antecedents: job characteristic, rewards and recognitions, distributive justice, procedural justice, perceived organizational support (POS), and perceived supervisor support (PSS) to job and organization engagements. This research was completed by 81 respondents working in University X. 54 percent respondent were female and majority is a lecturer (57 percent). This research included measures of job and organization engagement as well as the antecedents of engagement who developed by Saks (2006) for his research. The findings of this research is all antecedents’ not significant influence job engagement while only POS positive significant influence organizational engagement. Those findings proved that job and organizational engagement are two different construct and contributed to strengthening research on management especially in engagement study.